An Effective Primary Head and Neck Squamous Cell Carcinoma In Vitro Model - Oppel, Felix (Cells, 2019)
Head and neck squamous cell carcinoma is a highly malignant disease and research is needed to find new therapeutic approaches. Faithful experimental models are required for this purpose. Here, we describe the specific cell culture conditions enabling the efficient establishment of primary cell culture models. Whereas a classical 10% serum-containing medium resulted in the growth of fibroblast-like cells that outcompeted epithelial cells, we found that the use of specific culture conditions enabled the growth of epithelial tumor cells from HPV+ and HPV− head and neck cancer tissue applicable for research. EpCAM and high Thy-1 positivity on the cell surface were mutually exclusive and distinguished epithelial and fibroblast-like subpopulations in all primary cultures examined and thus can be used to monitor stromal contamination and epithelial cell content. Interestingly, cells of an individual patient developed tumor spheroids in suspension without the use of ultra-low attachment plates, whereas all other samples exclusively formed adherent cell layers. Spheroid cells were highly positive for ALDH1A1 and hence displayed a phenotype reminiscent of tumor stem cells. Altogether, we present a system to establish valuable primary cell culture models from head and neck cancer tissue at high efficiency that might be applicable in other tumor entities as well.